Lone (loan) wolf pack risk - Mingze Gao; Iftekhar Hasan; Buhui Qiu; Eliza Wu (Bank of Finland, 2023)
This paper proposes an early-warning bank risk measure based on the syndicate concentration of recent syndicated loans that a bank participates in. At the bank level, higher values of the measure predict greater risks (i.e., loan loss provisions, idiosyncratic return volatility, default probability, and frequency of lawsuits) and lower profitability at least three years ahead, especially for opaque and complex banks. Banks failing the Federal Reserve's forward-looking stress tests subsequently exhibit a reduction in the syndicate concentration measure. At the aggregate level, higher values of the measure predict both greater financial sector risks and economic slowdowns measured by private-sector investment, business activity, total factor productivity, industrial production, and gross domestic product.
Keywords: G21; E02; 330; syndicate concentration; early-warning; bank risks; financial sector risks; economic slowdowns